Efficacy of CytoSorb in a Pediatric Case of Severe Multisystem Infammatory Syndrome (MIS-C): A Clinical Case Report - Bottari, Gabriella; Confalone, Valerio; Cotugno, Nicola; Guzzo, Isabella; Perdichizzi, Salvatore; Manno, Emma C.; Stoppa, Francesca; Cecchetti, Corrado (Frontiers in Pediatrics, 2021)
Background. Multisystem inflammatory syndrome in children (MIS-C) has emerged during the COVID-19 pandemic as a new SARS-CoV-2-related entity, potentially responsible for a life-threatening clinical condition associated with myocardial dysfunction and refractory shock. Case. We describe for the first time in a 14 year old girl with severe MIS-C the potential benefit of an adjuvant therapy based on Cytosorb hemoperfusion and Continuous Renal Replacement Therapy with immune-modulatory drugs. Conclusions. We show in our case that from the start of extracorporeal blood purification, there was a rapid and progressive restoration in cardiac function and hemodynamic parameters in association with a reduction in the most important inflammatory biomarkers (Interleukin 6, Interleukin 10, C-reactive protein, Ferritin, D-dimers). Additionally, for the first time we were able to show with the analysis of the sublingual microcirculation, a delayed improvement in most of the important microcirculation parameters in this clinical case of MIS-C.